Nursing care for peptic ulcer patients following the nursing process - Radulović Vedrana (Sestrinska reč, 2019)
INTRODUCTION: Peptic ulcer is a group of upper gastrointestinal ulcer diseases in which the aggressive effect of hydrochloric acid and pepsin on the mucous membrane of this system plays the most significant role. The two most common causes of peptic ulcer are Helicobacter pylori eradication and overuse of non-steroidal anti-inflammatory drugs. In this paper is presented the patient with duodenal ulcer treated at the University Hospital Foča in the Department of Gastroenterology. VIEW OF THE PATIENT: Patient aware, oriented, acting exhausted, shortness of breath, moderately nourished, afebrile, acyanotic, pronounced general weakness and languor, gait instability and dizziness. Pulse 100/min,TA 160/100mmhg. The troubles began with a feeling of nausea, and three days before admission he threw up dark contents. After that he had a dark excrement on a couple of occasions. The problems became more and more acute, and after the laboratory analyzes he was sent to the University Hospital in Foca. States that he has been drinking a lot of pain medication for 4-5 months because of the severity of his spine pain(isialgia). Receives hypertension medications. The patient's mother had stomach problems, denied allergies, and food or medication. The patient gave us information that he is a non-smoker and occasionally he consumed alcohol. Chronic cough and thick cough expectoration are present, lasting for a long period. After a thorough history, a physical examination of the findings of the esophagogastroduodenoscopy, the gastroenterologist made the diagnosis - Ulcer of the duodenum. CONCLUSION: After the completion of hospitalization, the patient's physical and mental condition improved significantly. The patient expressed satisfaction with the quality of health services, information received, health care and hospital treatment.